Identifying barriers to healthy eating and physical activity in a low-income community in south-western Kansas - Kumar, Janavi (Kansas State University, 2013)
Obesity in adolescence is associated with a complex web of ecological, psychosocial, and physiological factors, and many of these factors relate to nutrition and physical activity behaviors. Before interventions are developed, researchers need to know what factors specifically influence an adolescent’s food choices and physical activity within the community context. Cultural norms, school environment, and neighborhood attributes are examples of factors that may vary across different communities, and accounting for this variation can be quite challenging, unless community perspectives are acknowledged. The use of qualitative data from focus groups has shown to be an effective way of gathering community perspectives about the diversity of their views and experiences. The current study used focus groups to reveal facilitators and barriers to healthy eating behavior and physical activity engagement in 6th to 8th grade youth in a low-income community in South-Western Kansas. This methodology enabled community members (adolescents, parents, and teachers) to discuss and articulate their perceptions in relation to 6th to 8th grade youth’s eating habits and physical activity, and assessed available resources, needs, and opportunities for developing effective and sustainable intervention approaches in the community. Using the socio-ecological model, individual influences (e.g., taste preferences), social influences (e.g., parent and peer influences), and larger contextual influences (e.g., school) on early adolescent health were assessed. This information will be used to develop interventions addressing factors at these different levels of influence that are needed to improve eating habits and physical activity of youth in the community.
Keywords: Childhood obesity; Socio-ecological model; Focus groups; Qualitative research; Sensory; Health; Health Education (0680); Nutrition (0570); Public Health (0573)